Randomised controlled trial of homoeopathy versus placebo in perennial allergic rhinitis with overview of four trial series - Taylor, Morag A (BMJ Group, 2000)
OBJECTIVE: To test the hypothesis that homoeopathy is a placebo by examining its effect in patients with allergic rhinitis and so contest the evidence from three previous trials in this series. DESIGN: Randomised, double blind, placebo controlled, parallel group, multicentre study. SETTING: Four general practices and a hospital ear, nose, and throat outpatient department. PARTICIPANTS: 51 patients with perennial allergic rhinitis. INTERVENTION: Random assignment to an oral 30c homoeopathic preparation of principal inhalant allergen or to placebo. MAIN OUTCOME MEASURES: Changes from baseline in nasal inspiratory peak flow and symptom visual analogue scale score over third and fourth weeks after randomisation. RESULTS: Fifty patients completed the study. The homoeopathy group had a significant objective improvement in nasal airflow compared with the placebo group (mean difference 19.8 l/min, 95% confidence interval 10.4 to 29.1, P=0.0001). Both groups reported improvement in symptoms, with patients taking homoeopathy reporting more improvement in all but one of the centres, which had more patients with aggravations. On average no significant difference between the groups was seen on visual analogue scale scores. Initial aggravations of rhinitis symptoms were more common with homoeopathy than placebo (7 (30%) v 2 (7%), P=0.04). Addition of these results to those of three previous trials (n=253) showed a mean symptom reduction on visual analogue scores of 28% (10.9 mm) for homoeopathy compared with 3% (1.1 mm) for placebo (95% confidence interval 4.2 to 15.4, P=0.0007). CONCLUSION: The objective results reinforce earlier evidence that homoeopathic dilutions differ from placebo.